A Randomized Trial of User-Controlled Text Messaging to Improve Asthma Outcomes: A Pilot Study. (December 2017) - Britto, Maria T.; Rohan, Jennifer M.; Dodds, Cassandra M.; Byczkowski, Terri L.
We enrolled 64 patients age 12 to 22 years with a diagnosis of poorly controlled persistent asthma in a 6-month longitudinal crossover study. During the 3 intervention months, participants created personalized text messages to be sent to their phones. Adherence was objectively monitored in 22 of the participants. The adolescent participants gave high ratings on the acceptability of the text messaging system. Asthma control improved from baseline to month 1 regardless of whether teens were in the texting or control group. While participants were in the texting group, their quality of life improved and worry about their asthma decreased. Receiving the text intervention resulted in an increase in adherence of 2.75% each month relative to no intervention, but the improvements were not sustained. There was modest improvement in asthma control and quality of life outcomes, as well as improved adherence during the texting intervention.